2009
DOI: 10.1007/s11060-009-9816-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of alternative splicing of the D2 dopamine receptor mRNA and estrogen receptor mRNA in the prolactinomas and gonadotrope tumors

Abstract: This study for the first time shows a good correlation between expression of ER and D2R isoforms in prolactinomas and gonadotrope tumors. Reducing the amount of the ERalpha in neoplasm cells can alter the ratio of D2L/D2S, which may increase the drug sensitivity of pituitary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Our data supported the findings of Wu et al [41] reporting that 17β-estradiol acted to modulate the ratio of the two isoforms of the dopamine D2 receptor (D2L/D2S), by transcription of their respective genes, through nuclear estrogen receptors induction, thereby highlighting functional difference between the two isoforms. The two isoforms coexisted in most brain tissue analyzed and the ratio of D2L versus D2S mRNA expressions varied from region to region [88] [89].…”
Section: A Bâ Et Al Journal Of Behavioral and Brain Sciencesupporting
confidence: 92%
See 1 more Smart Citation
“…Our data supported the findings of Wu et al [41] reporting that 17β-estradiol acted to modulate the ratio of the two isoforms of the dopamine D2 receptor (D2L/D2S), by transcription of their respective genes, through nuclear estrogen receptors induction, thereby highlighting functional difference between the two isoforms. The two isoforms coexisted in most brain tissue analyzed and the ratio of D2L versus D2S mRNA expressions varied from region to region [88] [89].…”
Section: A Bâ Et Al Journal Of Behavioral and Brain Sciencesupporting
confidence: 92%
“…For instance, the 17β-estradiol regulated through its slow genomic actions, the transcription and synthesis of both D2L and D2S isoforms [40] [41].…”
Section: Introductionmentioning
confidence: 99%
“…E 2 is known to affect D2 receptor splicing and increases the ratio of D2L and D2S receptor numbers or mRNA levels in lactotropes (Guivarc'h et al 1998, Oomizu et al 2003. This differential splicing of D2 receptor isoforms might be a critical mechanism of E 2 action on lactotropes, as a negative correlation between D2S and ERa mRNA expression and a positive correlation between D2L and ERa mRNA expression were found in human prolactinomas (Wu et al 2009). The data obtained from this study also indicated that E 2 was able to markedly increase PRL production and cell proliferation in cells expressing D2S receptor but produced a very moderate effect in cells producing D2L receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol induces tyrosine hydroxylase gene transcription with estradiol receptor-alpha (ER-alpha), [9], requiring cAMP/calcium responses and protein kinase pathways [15], thereby increases activation of dopamine neurons [16]. For instance, the 17β-estradiol regulated through its slow Journal of Biosciences and Medicines genomic actions, the transcription and synthesis of both D2L and D2S dopamine receptors isoforms [18] [19].…”
Section: Introductionmentioning
confidence: 99%